Analytical Analysis of Dynamic Wireless Power Transfer System Controllers for Electric Vehicles: A Review - Aveen Uthman Hassan; Fadhil T. Aula (Applications of Modelling and Simulation)
The increase in the Electric Vehicle (EV) market is driven by the desire for more efficient and reliable approaches in charging EV batteries. Among various charging methodologies for EVs, Dynamic Wireless Power Transfer (DWPT) has recently been considered as a promising solution to alleviate the range anxiety and long-charging-duration issue of EVs on highways. However, modeling, controlling, and analyzing the DWPT system are highly challenging because the system dynamics in underlying power system and transportation system have to be jointly considered that makes the problem highly complicated. Thence, the role of advanced control systems becomes increasingly vital in optimizing power transfer efficiency, ensuring system stability, and enhancing user safety. This review systematically categorizes and examines various control strategies employed in DWPT systems, including frequency, phase, amplitude, and hybrid control methods. It delves into the mathematical models and analytical techniques that are used to evaluate these controllers, offering a comparative analysis of their performance metrics such as efficiency, power transfer capability, and robustness. The review also addresses the technical challenges faced with the practical implementation of these systems and identifies current research gaps and future recommendations. By synthesizing the latest advancements and providing critical insights, this review aims to guide future research and development efforts in the field of DWPT systems for EVs.